Endothelial dysfunction aggravates arterial media calcification in warfarin administered rats. Issue 5 (15th April 2022) - Van den Bergh, Geoffrey; Van den Branden, Astrid; Opdebeeck, Britt; Fransen, Paul; Neven, Ellen; De Meyer, Guido R.Y.; D'Haese, Patrick C.; Verhulst, Anja
Abstract: Arterial media calcification is an active cell process. This encompasses osteochondrogenic transdifferentiation of vascular smooth muscle cells followed by the deposition of calcium‐phosphate crystals. Increasing evidence suggests a significant role for endothelial cells (ECs) in the development of arterial media calcification. This manuscript explores a role for endothelial dysfunction in the disease progression of arterial media calcification. Male rats were randomly assigned to four different groups. The first group received standard chow. The second group was given L‐NAME (≈50 mg kg −1 · d −1 ), to induce endothelial dysfunction, in addition to standard chow. The third group and fourth group received a warfarin‐supplemented diet to induce mild calcification and the latter group was co‐administered L‐NAME. Prior to sacrifice, non‐invasive measurement of aortic distensibility was performed. Animals were sacrificed after 6 weeks. Arterial media calcification was quantified by measuring aortic calcium and visualized on paraffin‐embedded slices by the Von Kossa method. Arterial stiffness and aortic reactivity was assessed on isolated carotid segments using specialized organ chamber setups. Warfarin administration induced mineralization. Simultaneous administration of warfarin and L‐NAME aggravated the arterial media calcification process. Through organ chamber experiments an increased vessel tonus was found, which could be linked to reduced basal NO availability, in arteries of warfarin‐treated animals. Furthermore, increased calcification because of L‐NAME administration was related to a further compromised endothelial function (next to deteriorated basal NO release also deteriorated stimulated NO release). Our findings suggest early EC changes to impact the disease progression of arterial media calcification.